AWARENESS AND KNOWLEDGE OF PHYSICAL THERAPY AMONG MEDICAL INTERNS A PILOT STUDY (International Journal of Physiotherapy, 2016)
Background: The changes happening in the physical therapy education and the profession should be reached and demand to be seen by the other medical professionals to benefit the health care process. At the same time, if attempts are to be prepared to elevate the degree of awareness of physical therapy, it is necessary to evaluate the current attitude and knowledge of the medical interns. So the aim of this study was to find out the current level of awareness and knowledge about physical therapy among the M.B.B.S. medical interns.Methods: An institution based cross sectional study, carried out purely based on the questionnaire method which consist of sets of questions. Prior to the data collection the researcher explained about the study to the subject and an informed consent was obtained from them. The researcher gave the questionnaire form to the subject and was required to fill the frame. The data collected was analysed by using frequency and percentage in IBM SPSS statistics V 19.Results: Only 45% of medical interns had awareness and 42% had knowledge about physical therapy.Conclusion: The results of the study provide information regarding the lack of awareness and knowledge among medical interns about physical therapy. Hence there is a need of educating the future medical professionals about the physical therapy, thereby reaching a better patient care.